Light emitting device
Through flip chip structure and gradient layer design, the challenges of UV LED light emitting elements in driving voltage rise and on-axis intensity increase are solved, and efficient light extraction and stable driving voltage are achieved, which are suitable for UV LED applications.
Patent Information
- Application Number
- CN202410768547.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-16
- Filing Date
- 2024-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing ultraviolet LED light emitting elements have challenges in driving voltage rise and on-axis intensity increase, especially the problems of driving voltage changes and low lateral light extraction efficiency due to changes in the thickness of the semiconductor layer.
The flip chip type ultraviolet luminescent element is adopted, and the sealing part with a refractive index higher than air but lower than the element is covered on the upper surface of the light emitting element, and the lens with a refractive index higher than the sealing part is covered thereon, combining the gradient layer and p The design of the contact layer is to control the interference of ultraviolet light to increase the on-axis intensity and suppress the rise of the driving voltage.
It effectively improves the on-axis intensity of the light emitting element, suppresses the increase in driving voltage, improves the light extraction efficiency and the width of the emission angle, and is suitable for practical applications.
Smart Images

Figure CN119153600A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a light emitting device. Background Art
[0002] The wavelength of ultraviolet light of solid-state light-emitting elements using IIIA nitride semiconductors corresponds to a band of about 210 to 400 nm. It is known that UVC (wavelength 100 to 280 nm) can effectively sterilize and disinfect, and the demand for IIIA nitride semiconductor LEDs that emit ultraviolet light with a wavelength corresponding to UVC is increasing. Ultraviolet LEDs are composed of an AlN layer formed on a sapphire substrate, and an n-type layer, a light-emitting layer, and a p-type layer composed of AlGaN are stacked on the AlN layer.
[0003] Patent Document 1 states that the thickness of the semiconductor layer in the light-emitting element is n×d=m×λ / 2, where n is the refractive index of the semiconductor layer, d is the thickness of the semiconductor layer, λ is the emission wavelength, and m is an integer. It is also stated that by setting the thickness of the semiconductor layer in this way, the attenuation caused by light interference inside the element can be prevented, and the light extraction efficiency can be improved.
[0004] Patent document 2 describes that a composition gradient layer is provided between the electron blocking layer and the p-type contact layer. The composition gradient layer is composed of AlN or AlGaN, and is formed in a manner that the Al composition decreases as it moves away from the electron blocking layer. The Al composition at the interface with the electron blocking layer is the same as that of the electron blocking layer. It is also described that by providing a composition gradient layer, the generation of two-dimensional hole gas can be suppressed, and the generation of current crowding can be suppressed.
[0005] Patent Document 3 describes a light emitting device in which an ultraviolet LED mounted on a mounting substrate is covered with a lens, and a gap between the ultraviolet LED and the lens is filled with a liquid carbon fluoride compound.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-119756
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-16964
[0010] Patent Document 3: Japanese Patent Application Publication No. 2022-108692 Summary of the invention
[0011] However, Patent Documents 1-3 do not mention the angular dependence (light distribution) of light extracted from the light-emitting element. For example, light extracted in the lateral direction of the light-emitting element (in the direction horizontal to the main surface of the light-emitting element) is difficult to apply in actual products. Therefore, it is required to improve the on-axis intensity (light intensity in the direction perpendicular to the main surface of the light-emitting element) in the internal structure of the element. In addition, in the method of Patent Document 1, since the series resistance varies with the thickness of the semiconductor layer, the driving voltage may also vary.
[0012] The present invention has been made in view of the above background, and an object of the present invention is to provide a light emitting device capable of suppressing an increase in driving voltage and improving on-axis intensity.
[0013] One embodiment of the present invention relates to a light emitting device having:
[0014] A flip chip type ultraviolet light emitting element,
[0015] a sealing portion that contacts and covers at least the upper surface of the light emitting element and has a refractive index higher than that of air and lower than that of the light emitting element, and
[0016] a lens that contacts and covers the sealing portion and has a higher refractive index than the sealing portion,
[0017] The above-mentioned light emitting element has:
[0018] The n-type layer is composed of an n-type Group IIIA nitride semiconductor containing Al.
[0019] The active layer is located on the side opposite to the sealing portion of the main surface of the n-type layer, is composed of a IIIA group nitride semiconductor containing Al, and has a quantum well structure having a well layer and a barrier layer.
[0020] an electron blocking layer located on a side of the main surface of the active layer opposite to the n-type layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition is higher than that of the barrier layer,
[0021] a composition gradient layer, located on a side of the main surface of the electron blocking layer opposite to the active layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition decreases as the distance from the active layer increases;
[0022] a p-type contact layer located on the side of the main surface of the composition gradient layer opposite to the electron blocking layer, and composed of a p-type IIIA group nitride semiconductor containing Al; and
[0023] The p-side electrode is located on the side opposite to the composition gradient layer in the main surface of the p-type contact layer, and reflects the ultraviolet light from the active layer.
[0024] The thickness of the composition gradient layer is set so that light emitted from the active layer to the n-type layer side is enhanced in a direction perpendicular to the main surface of the light-emitting element through interference, followed by light emitted from the active layer to the side opposite to the n-type layer and then reflected by the p-side electrode to the n-type layer side.
[0025] Another aspect of the present invention relates to a method for manufacturing a light-emitting device, the light-emitting device comprising:
[0026] A flip chip type ultraviolet light emitting element,
[0027] a sealing portion that contacts and covers at least the upper surface of the light emitting element and has a refractive index higher than that of air and lower than that of the light emitting element, and
[0028] a lens that contacts and covers the sealing portion and has a higher refractive index than the sealing portion,
[0029] The above-mentioned light emitting element has:
[0030] The n-type layer is composed of an n-type Group IIIA nitride semiconductor containing Al.
[0031] The active layer is located on the side opposite to the sealing portion of the main surface of the n-type layer, is composed of a IIIA group nitride semiconductor containing Al, and has a quantum well structure having a well layer and a barrier layer.
[0032] an electron blocking layer located on a side of the main surface of the active layer opposite to the n-type layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition is higher than that of the barrier layer,
[0033] a composition gradient layer, located on a side of the main surface of the electron blocking layer opposite to the active layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition decreases as the distance from the active layer increases;
[0034] a p-type contact layer located on the side of the main surface of the composition gradient layer opposite to the electron blocking layer, and composed of a p-type IIIA group nitride semiconductor containing Al; and
[0035] The p-side electrode is located on the side opposite to the composition gradient layer in the main surface of the p-type contact layer, and reflects the ultraviolet light from the active layer.
[0036] The thickness of the composition gradient layer is set so that light emitted from the active layer toward the n-type layer side is enhanced in a direction perpendicular to the main surface of the light-emitting element through interference after being reflected by the p-side electrode from the active layer toward the side opposite to the n-type layer.
[0037] In the above-mentioned embodiment, the interference of ultraviolet light is controlled by the thickness of the composition gradient layer, so that the increase of the driving voltage can be suppressed and the on-axis strength can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a cross-sectional view schematically showing the structure of the light-emitting device in Embodiment 1, and is a view showing a cross section perpendicular to the main surface of the light-emitting element.
[0039] Figure 2 It is a cross-sectional view showing the structure of a light-emitting element, and is a view showing a cross section perpendicular to a main surface of the light-emitting element.
[0040] Figure 3 (a) is a diagram schematically showing the path of light inside a model in which AlN, sapphire, air, and a lens (quartz) are stacked in this order from the active layer side on an active layer. Figure 3 (b) is a diagram schematically showing the path of light inside a model having a structure in which AlN, sapphire, fluorine oil, and a lens (quartz) are stacked in this order from the active layer side on an active layer.
[0041] Figure 4 (a) is a graph showing the angular dependence of light output for a simplified model of a light emitting element, Figure 4 (b) is a graph showing the thickness dependency of the p-type layer for a simplified model of the light-emitting element.
[0042] Figure 5 This is a graph showing the calculation results and measurement results of the light output of the light emitting element.
[0043] Figure 6 This is a graph showing the results of measuring light output of a light-emitting device in which a light-emitting element is packaged.
[0044] Figure 7 This is a graph showing the results of measuring the increase rate of on-axis intensity and the width of the emission angle for a light-emitting device in which a light-emitting element is packaged.
[0045] Figure 8 This is a graph showing the results of calculating the light output from the top surface and the light output from the side surface of the light emitting element.
[0046] Fig. 9 (a) is a diagram showing the energy band diagram of the light-emitting element and the distribution of carrier concentration in the thickness direction when no voltage is applied, Fig. 9 (b) is a diagram showing an energy band diagram of the light-emitting element when 6 V is applied and a thickness direction distribution of carrier concentration.
[0047] Fig.10This is a graph showing the transmittance, absorptivity, and reflectivity of sapphire.
[0048] Fig.11 It is a graph showing the transmittance, absorptivity, and reflectivity of the AlN template.
[0049] Fig.12 It is a graph showing the transmittance, absorptance, and reflectance of the entire region from the substrate to the p-type contact layer.
[0050] Fig.13 This is a graph showing the transmittance, absorptivity, and reflectivity of undoped AlGaN.
[0051] Fig.14 It is a graph showing the transmittance, absorptivity, and reflectivity of Si-doped AlGaN.
[0052] Fig.15 It is a graph showing the transmittance, absorptivity, and reflectivity of Mg-doped AlGaN.
[0053] Fig.16 is a graph showing the transmittance, absorptivity, and reflectivity of a compositionally graded layer.
[0054] Fig.17 It is a graph showing the reflectivity of the p-side electrode.
[0055] Fig.18 It is a cross-sectional view schematically showing the structure of a light-emitting device in a modified form of Embodiment 1, and is a view showing a cross section perpendicular to a main surface of a light-emitting element.
[0056] Explanation of symbols
[0057] 1: Light-emitting element
[0058] 2: Sealing part
[0059] 3: Lens
[0060] 4: Install the baseboard
[0061] 10: Substrate
[0062] 11: n-type layer
[0063] 12: Active layer
[0064] 13: Electron blocking layer
[0065] 13A: 1st electron blocking layer
[0066] 13B: Second electron blocking layer
[0067] 14: Composition gradient layer
[0068] 14A: 1st composition gradient layer
[0069] 14B: 2nd composition gradient layer
[0070] 15: p-type contact layer
[0071] 16: p-side electrode
[0072] 17: n-side electrode DETAILED DESCRIPTION
[0073] The light emitting device comprises: a flip-chip type ultraviolet light emitting element, a sealing portion which contacts and covers at least the upper surface of the light emitting element and has a refractive index higher than that of air and lower than that of the light emitting element, and a lens which contacts and covers the sealing portion and has a refractive index higher than that of the sealing portion.
[0074] Moreover, the light-emitting element comprises: an n-type layer, which is composed of an n-type IIIA nitride semiconductor containing Al; an active layer, which is located on the surface of the main surface of the n-type layer on the side opposite to the sealing portion side, and is composed of a IIIA nitride semiconductor containing Al, and is a quantum well structure having a well layer and a barrier layer; an electron blocking layer, which is located on the surface of the main surface of the active layer on the side opposite to the n-type layer side, and is composed of a p-type IIIA nitride semiconductor containing Al, and the Al composition is higher than that of the barrier layer; a composition gradient layer, which is located on the surface of the main surface of the electron blocking layer on the side opposite to the active layer side, and is composed of a p-type IIIA nitride semiconductor containing Al, and the Al composition decreases with distance from the active layer; a p-type contact layer, which is located on the surface of the main surface of the composition gradient layer on the side opposite to the electron blocking layer side, and is composed of a p-type IIIA nitride semiconductor containing Al; and a p-side electrode, which is located on the surface of the main surface of the p-type contact layer on the side opposite to the above-mentioned composition gradient layer side, and reflects ultraviolet light from the above-mentioned active layer.
[0075] It should be noted that the thickness of the composition gradient layer is set so that light emitted from the active layer to the n-type layer side and light emitted from the active layer to the side opposite to the n-type layer and then reflected by the p-side electrode and emitted to the n-type layer side are enhanced through interference in a direction perpendicular to the main surface of the light-emitting element.
[0076] In the above-mentioned light-emitting device, the total film thickness from the uppermost layer in the barrier layer to the p-type contact layer is set to d1, and the thickness of the composition gradient layer is set to d2. The thickness d2 can be set in a way that d1 satisfies n×d1=m×λ (where n is the average refractive index of the layers from the electron blocking layer to the p-type contact layer at the light-emitting wavelength, and λ is the light-emitting wavelength), and m is 0.55 to 0.9.
[0077] The composition gradient layer can be a structure in which the first composition gradient layer and the second composition gradient layer are stacked in sequence from the electron blocking layer side. The first composition gradient layer can be undoped or doped with p-type impurities, and the second composition gradient layer can be doped with p-type impurities and the p-type impurity concentration is higher than that of the first composition gradient layer.
[0078] The thickness of the composition gradient layer can be set according to the thickness of the first composition gradient layer.
[0079] The ratio of the thickness of the first composition gradient layer to the thickness d2 of the composition gradient layer may be 0.4 to 0.7.
[0080] The sealing portion may be provided on the upper surface of the light emitting element, but not on the side surface.
[0081] The electron blocking layer may have a structure in which a first electron blocking layer and a second electron blocking layer are stacked in order from the active layer side. The Al composition of the second electron blocking layer may be lower than that of the first electron blocking layer and lower than the maximum Al composition of the composition gradient layer.
[0082] The invention discloses a method for manufacturing a light-emitting device, which comprises a flip-chip type ultraviolet light-emitting element, a sealing portion which contacts and covers at least the upper surface of the light-emitting element and has a refractive index higher than that of air and lower than that of the light-emitting element, and a lens which contacts and covers the sealing portion and has a refractive index higher than that of the sealing portion. Moreover, the light-emitting element comprises: an n-type layer, which is composed of an n-type IIIA nitride semiconductor containing Al; an active layer, which is located on the surface of the main surface of the n-type layer on the side opposite to the sealing portion side, and is composed of a IIIA nitride semiconductor containing Al, and is a quantum well structure having a well layer and a barrier layer; an electron blocking layer, which is located on the surface of the main surface of the active layer on the side opposite to the n-type layer side, and is composed of a p-type IIIA nitride semiconductor containing Al, and the Al composition is higher than that of the barrier layer; a composition gradient layer, which is located on the surface of the main surface of the electron blocking layer on the side opposite to the active layer side, and is composed of a p-type IIIA nitride semiconductor containing Al, and the Al composition decreases with distance from the active layer; a p-type contact layer, which is located on the surface of the main surface of the composition gradient layer on the side opposite to the electron blocking layer side, and is composed of a p-type IIIA nitride semiconductor containing Al; and a p-side electrode, which is located on the surface of the main surface of the p-type contact layer on the side opposite to the composition gradient layer side, and reflects ultraviolet light from the active layer. Moreover, the thickness of the composition gradient layer is set so that light emitted from the active layer to the n-type layer side and light emitted from the active layer to the side opposite to the n-type layer and then reflected by the p-side electrode to the n-type layer side are enhanced in a direction perpendicular to the main surface of the light-emitting element through interference.
[0083] The total film thickness from the topmost layer in the barrier layer to the p-type contact layer is set to d1, the thickness of the composition gradient layer is set to d2, and d3=d1-d2. The thickness d3 is fixed to a specified value, and the thickness d2 is changed. The thickness d2 can be set to satisfy n×d1=m×λ (where n is the average refractive index of the layers from the electron blocking layer to the p-type contact layer at the emission wavelength, and λ is the emission wavelength), and m is 0.55~0.9.
[0084] The composition gradient layer can be a structure in which a first composition gradient layer and a second composition gradient layer are stacked in sequence from the electron blocking layer side. The first composition gradient layer can be undoped or doped with p-type impurities, and the second composition gradient layer can be doped with p-type impurities and the p-type impurity concentration is higher than that of the first composition gradient layer. The thickness of the second composition gradient layer can be fixed to a specified value, and the thickness of the first composition gradient layer can be changed to set the thickness of the composition gradient layer.
[0085] (Implementation Method)
[0086] 1. Composition of the light-emitting device
[0087] Figure 1 2 is a cross-sectional view showing the structure of the light emitting device in the embodiment, and is a view showing a cross section in the axial direction. Figure 1 As shown, the light emitting device in Embodiment 1 includes a light emitting element 1 , a sealing portion 2 , a lens 3 , and a mounting substrate 4 .
[0088] The light-emitting element 1 is a light-emitting element using a group IIIA nitride semiconductor. The emission wavelength is, for example, 225 to 300 nm. The detailed structure of the light-emitting element 1 is described below. The light-emitting element 1 is a flip-chip type, one surface is a light extraction side, and the surface on the opposite side is an electrode side. The light-emitting element 1 is mounted on a mounting substrate 4. The upper surface of the light extraction surface of the light-emitting element 1 is the main surface, and the light output from the upper surface is greater than the light output from the side. Here, the upper surface of the light-emitting element 1 is the surface on the side opposite to the lower surface of the light-emitting element 1, and the lower surface is the surface on the mounting substrate 4 side of the light-emitting element 1, that is, the surface on the electrode forming side. The mounting substrate 4 is preferably a ceramic material with high heat dissipation such as AlN and SiC.
[0089] The sealing portion 2 is provided in a manner to fill the gap between the upper surface of the light emitting element 1 and the lens 3, and is provided to be in contact with the upper surface of the light emitting element 1 and the lens 3. The sealing portion 2 does not cover the side surface of the light emitting element 1. In addition, the sealing portion 2 preferably covers the entire upper surface of the light emitting element 1.
[0090] The refractive index of the sealing portion 2 is set to a value higher than the refractive index of air and lower than the refractive index of the light-emitting element 1. Here, the refractive index is a value at the emission wavelength. Hereinafter, unless otherwise specified in this specification, the same meaning shall apply. In addition, the refractive index of the light-emitting element 1 is the average refractive index of the entirety. For example, the refractive index of the sealing portion 2 is 1.2 to 1.6.
[0091] When an air layer is formed by a gap between the upper surface of the light emitting element 1 and the lens 3, the difference in refractive index between the light emitting element 1 and the air is large, and the critical angle of total reflection at the interface between the upper surface of the light emitting element 1 and the air layer is small. As a result, the emission angle of ultraviolet light that can be extracted from the light emitting element 1 is narrow, and the ratio of light incident from the light emitting element 1 to the lens 3 is low.
[0092] On the other hand, if the sealing portion 2 having the above-mentioned refractive index is provided between the upper surface of the light-emitting element 1 and the lens 3, the difference in refractive index between the light-emitting element 1 and the sealing portion 2 becomes smaller, and thus the critical angle of total reflection at the interface between the upper surface of the light-emitting element 1 and the sealing portion 2 becomes larger. As a result, the emission angle of ultraviolet light that can be extracted from the light-emitting element 1 is widened, and the incident efficiency of light from the light-emitting element 1 to the lens 3 can be improved.
[0093] The material of the sealing portion 2 can be any material as long as it is a material that is translucent to the ultraviolet light emitted from the light-emitting element 1, and can be a liquid or a solid. Preferably, a material that does not deteriorate to the ultraviolet light emitted from the light-emitting element 1 is used. For example, organic halides, UVC-transmitting glass silicone resins, etc. can be used. As liquid organic halides, silicone oil can be used. As solid organic halides, amorphous fluororesins, FEP, PFA and other fluororesins can be used.
[0094] As the material of the sealing portion 2, a fluorinated carbon compound is particularly preferred. A fluorinated carbon compound is a polymer having a C-F bond. The fluorinated carbon compound may be a compound (fluorinated oil) that is liquid at room temperature and pressure, or may be solid. The number of carbon atoms in the fluorinated carbon compound may be less than 1.9 times the number of fluorine atoms in the fluorinated carbon compound. Examples of fluorinated carbon compounds include perfluoropolyether (PFPE), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (PEP), tetrafluoroethylene-ethylene copolymer (ETFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), polychlorotrifluoroethylene (PCTFE), and the like.
[0095] In addition, the sealing part 2 may be a fluororesin film. In addition, the liquid fluorinated carbon compound may be covered and sealed with a fluororesin film. The material of the fluororesin film is, for example, FEP, PFA, PCTFE, etc.
[0096] In addition, when the material of the sealing part 2 is liquid, a filler can be mixed to adjust the viscosity. The filler is a material that does not absorb ultraviolet light, or the particle size is adjusted in a way that does not absorb ultraviolet light. The material of the filler is, for example, fluororesin powder or silicon dioxide. The refractive index of the filler is preferably the same as the refractive index of the sealing part 2, for example, 1.2 to 1.6.
[0097] The thickness and refractive index of the sealing portion 2 may be values that allow the sealing portion 2 to function as an antireflection film that prevents reflection between the light emitting element 1 and the lens 3. For example, the refractive index of the sealing portion 2 may be higher than that of the lens 3 and lower than that of the light emitting element 1, and the thickness of the sealing portion 2 may be 1 / 4 of the emission wavelength. This further improves the light extraction efficiency from the light emitting element 1 and can further improve the on-axis intensity.
[0098] The lens 3 is provided on the mounting substrate 4 in a manner covering the side surface of the light emitting element 1 and the sealing portion 2. The lens 3 is in contact with the sealing portion 2. In addition, the side surface of the light emitting element 1 may be in contact with the lens 3, or an air layer may be provided between the side surface of the light emitting element 1 and the lens 3. By providing the air layer, it is possible to increase the total reflection at the side surface of the light emitting element 1 and improve the light extraction from the upper surface of the light emitting element 1. The lens 3 and the mounting substrate 4 are bonded by an adhesive not shown.
[0099] The surface of the lens 3 is spherical or parabolic. With the lens 3 having such a shape, light emitted from the upper surface of the light emitting element 1 is refracted in the on-axis direction and emitted from the lens 3. Therefore, the light intensity in the on-axis direction can be increased.
[0100] The material of the lens 3 can be any material as long as it is transparent to the ultraviolet light emitted from the light emitting element 1 and is not degraded by the ultraviolet light. For example, it can be a transparent ceramic such as quartz glass, glass, silicone, fluororesin, sapphire, etc. In addition, the refractive index of the lens 3 can be any value as long as it is greater than the refractive index of the sealing portion 2. For example, the refractive index of the lens 3 is greater than 1.4.
[0101] In the light emitting device of Embodiment 1, since the sealing portion 2 is provided between the upper surface of the light emitting element 1 and the lens 3, the on-axis strength can be improved. In particular, the structure of the light emitting element 1 is designed so that the on-axis strength of the light emitting device becomes high in consideration of the total reflection between the upper surface of the light emitting element 1 and the sealing portion 2. The structure of the light emitting element 1 is described in detail below.
[0102] 2. Configuration of Light Emitting Element 1
[0103] Figure 2 1 is a cross-sectional view showing the structure of the light emitting element 1, and is a view showing a cross section in a direction perpendicular to the main surface of the substrate. Figure 2As shown, the light emitting element involved in the embodiment comprises: a substrate 10, an n-type layer 11, an active layer 12, an electron blocking layer 13, a composition gradient layer 14, a p-type contact layer 15, a p-side electrode 16 and an n-side electrode 17. The light emitting element in the embodiment is a flip chip type, and the light emission wavelength is in the UVC band.
[0104] The substrate 10 is a substrate composed of sapphire with the c-plane as the main surface. The crystal orientation of the main surface of the sapphire can be the a-plane. In addition, it can have a deviation angle of 0.1 to 2 degrees in the m-axis direction. The back side of the substrate 10 (the surface on the side opposite to the n-type layer 11) becomes the main light extraction surface. An anti-reflection film can be provided on the back side of the substrate 10 to achieve an increase in the light extraction rate. In addition, bumps and depressions can be provided on the surface of the substrate 10 to achieve an increase in the light extraction rate. In addition, as the substrate 10, an AlN template substrate having an AlN layer formed on an AlN substrate or a sapphire substrate can be used.
[0105] The thickness of the substrate 10 is, for example, 1000 μm or less, preferably 500 μm or less. This can suppress light extraction from the side surfaces of the substrate 10 and improve the on-axis strength.
[0106] It should be noted that the substrate 10 can be removed by a method such as LLO (laser lift off).
[0107] The n-type layer 11 is located on the substrate 10. The n-type layer 11 is composed of n-AlGaN. The Al composition (the molar ratio of Al in the entire group IIIA metal) is, for example, 60 to 90%. The n-type impurity is Si, and the Si concentration is, for example, 1×10 18 ~5×10 19 cm -3 The thickness of the n-type layer 11 is, for example, 0.5 to 5 μm. In addition, the C concentration of the n-type layer 11 is 1×10 15 ~1×10 19 cm -3 The n-type layer 11 may be composed of a plurality of layers. For example, it may be a superlattice layer composed of alternately stacked AlGaN layers having different Al compositions. In addition, a base layer composed of AlN may be provided between the substrate 10 and the n-type layer 11. In addition, a substance other than Si may be used as the n-type impurity.
[0108] In addition, the Al composition of the n-type layer 11 may be set to increase toward the substrate 10. The n-type layer 11 can function as a lens according to the refractive index distribution, and the on-axis intensity of the light emitting element 1 can be further improved.
[0109] The active layer 12 is located on the n-type layer 11. The active layer 12 has an SQW structure in which a barrier layer, a well layer, and a barrier layer are stacked in this order from the n-type layer 11 side. The active layer 12 may also have an MQW structure. In this case, the number of repetitions is, for example, 2 to 10.
[0110] The well layer is made of AlGaN, and its Al composition can be set according to the desired emission wavelength. The Si concentration of the well layer is, for example, 1×10 18 cm -3 In the following, no doping may be required. In addition, the thickness of the well layer is, for example, 0.5 to 5 nm.
[0111] The barrier layer is AlGaN with a higher Al content than the well layer, and the Al content is, for example, 50 to 100%. The Si concentration of the barrier layer is, for example, 2×10 19 cm -3 The following may be undoped. The thickness of the barrier layer is, for example, 3 to 30 nm. The barrier layer may be AlGaInN having a larger band gap energy than the well layer. In addition, the layer in contact with the electron blocking layer 13 in the barrier layer may have a thickness of 0.5 to 10 nm.
[0112] A hole blocking layer may be provided between the n-type layer 11 and the active layer 12. This can prevent holes injected from the p-side electrode 16 from diffusing to the n-type layer 11 side beyond the active layer 12. The hole blocking layer is AlGaN or AlN having a higher Al composition than the barrier layer of the active layer 12.
[0113] The electron blocking layer 13 is located on the active layer 12. The electron blocking layer 13 has a two-layer structure in which a first electron blocking layer 13A and a second electron blocking layer 13B are stacked in order from the active layer 12 side. The electron blocking layer 13 prevents electrons injected from the n-side electrode 17 from passing through the active layer 12 and diffusing to the composition gradient layer 14 side.
[0114] It should be noted that the electron blocking layer 13 does not necessarily have a two-layer structure, and may be only the first electron blocking layer 13A.
[0115] The first electron blocking layer 13A is made of AlGaN or AlN having a higher Al content than the barrier layer of the active layer 12, and the Al content is, for example, 90 to 100%. In addition, the first electron blocking layer 13A may be doped with a p-type impurity or may be undoped. The p-type impurity is, for example, Mg. When doped with Mg, the Mg concentration is, for example, 3×10 20 cm -3 The thickness of the first electron blocking layer 13A is, for example, 1 to 10 nm.
[0116] The second electron blocking layer 13B is composed of AlGaN with a lower Al composition than the first electron blocking layer 13A, and the Al composition is, for example, 80 to 99%. By providing the second electron blocking layer 13B, the difference in Al composition with the composition gradient layer 14 is adjusted. When the first electron blocking layer 13A is only AlN, the resistance becomes high. If the first electron blocking layer 13A is thin, the performance of blocking electrons decreases. Therefore, by providing the second electron blocking layer 13B, low resistance and electron blocking function are achieved. In addition, the second electron blocking layer 13B can be doped with p-type impurities or can be undoped. In the case of Mg doping, the Mg concentration is, for example, 3×10 20 cm -3 In addition, the thickness of the second electron blocking layer 13B is, for example, 1 to 10 nm.
[0117] The composition gradient layer 14 is located on the second electron blocking layer 13B. The composition gradient layer 14 has a two-layer structure in which a first composition gradient layer 14A and a second composition gradient layer 14B are stacked in this order from the electron blocking layer 13 side.
[0118] The composition gradient layer 14 is a p-type layer formed by a method called polarization doping. That is, the composition gradient layer 14 is a layer in which the Al composition changes in the thickness direction, and is set so that the Al composition decreases as it moves away from the electron blocking layer 13. It is difficult to increase the hole concentration of AlGaN with a high Al composition when doped with Mg, but the hole concentration can be increased by polarization doping, which can improve the injection efficiency of holes into the active layer 12. In addition, Mg can be omitted in polarization doping, so the crystallinity can be improved.
[0119] If the Al composition of the composition gradient layer 14 is set as described above, polarization caused by crystal strain is continuously generated in the thickness direction in the composition gradient layer 14. In order to offset the fixed charge generated by the polarization, holes are generated in the composition gradient layer 14. The generated holes are distributed in the composition gradient layer 14. Therefore, the holes are widely distributed in the thickness direction from the electron blocking layer 13 side in the composition gradient layer 14, and the whole becomes p-type. The hole concentration in this p-type region is 1×10 16 ~1×10 20 cm -3 The hole concentration decreases as the distance from the electron blocking layer 13 increases. The reason why the number of holes decreases near the interface of the p-type contact layer 15 of the composition gradient layer 14 is that the Fermi level tries to be consistent due to the p-type heterojunction, resulting in band bending.
[0120] The maximum Al composition of the first composition gradient layer 14A (Al composition at the interface with the electron blocking layer 13) is preferably 1 to 20% lower than the Al composition of the electron blocking layer 13. The hole concentration can be further increased by polarization caused by strain. For example, the maximum Al composition is 65 to 95%.
[0121] In addition, the minimum value of the Al composition of the first composition gradient layer 14A (the Al composition at the interface with the second composition gradient layer 14B) is preferably 3 to 30% lower than the maximum value of the Al composition of the first composition gradient layer 14A. The polarization caused by strain can be used to further increase the hole concentration. In addition, it is preferred that the Al composition has a band gap energy that does not absorb the emission wavelength.
[0122] The reduction rate of the Al composition is preferably 0.1 to 0.3% / nm. By setting it in this range, the hole concentration of the composition gradient layer 14 can be further increased. The reduction rate of the Al composition may be constant, that is, linearly changing, or non-constant.
[0123] The first composition gradient layer 14A is undoped. However, it can be doped with Mg. It is expected that the hole concentration can be further increased by using p-type impurities. In this case, the Mg concentration is, for example, 1×10 20 cm -3 On the other hand, from the viewpoint of suppressing the change in series resistance caused by the change in thickness of the first composition gradient layer 14A, the Mg concentration is preferably as low as possible, and non-doping is preferred.
[0124] The second composition gradient layer 14B is a layer having a higher Mg concentration than the first composition gradient layer 14A, and the Al composition is set in the same manner as the first composition gradient layer 14A. That is, the Al composition changes in the thickness direction and is set so that the Al composition decreases as the distance from the electron blocking layer 13 increases. By doping Mg in the second composition gradient layer 14B, it can be well connected to the p-type contact layer 15.
[0125] The difference between the maximum Al composition of the second composition gradient layer 14B (the Al composition at the interface with the first composition gradient layer 14A) and the minimum Al composition of the first composition gradient layer 14A is 0 to 5%, and is preferably the same as the minimum Al composition of the first composition gradient layer 14A. That is, it is preferred that the Al composition is continuous from the first composition gradient layer 14A to the second composition gradient layer 14B.
[0126] Furthermore, the minimum value of the Al composition of the second composition gradient layer 14B (the Al composition at the interface with the p-type contact layer 15 ) is preferably 3 to 30% lower than the maximum value of the Al composition of the second composition gradient layer 14B.
[0127] The reduction rate of the Al composition of the second composition gradient layer 14B is in the same range as the reduction rate of the Al composition of the first composition gradient layer 14A. The reduction rate of the Al composition of the second composition gradient layer 14B may be the same as the reduction rate of the Al composition of the first composition gradient layer 14A.
[0128] The Mg concentration of the second composition gradient layer 14B may be any value as long as it is higher than the Mg concentration of the first composition gradient layer 14A, but is preferably 3×10 20 cm -3 This is to suppress the series resistance.
[0129] In the first embodiment, the Al composition of the composition gradient layer 14 decreases continuously, but it may decrease stepwise. However, it is preferable that the region where the Al composition is constant is as small as possible.
[0130] The thickness of the composition gradient layer 14 is set to a thickness that intensifies the ultraviolet light emitted from the active layer 12 to the n-type layer 11 side and the ultraviolet light emitted from the active layer 12 to the electron blocking layer 13 side and reflected by the p-side electrode 16 and then emitted to the n-type layer 11 side in the axial direction through light interference. The details are described below.
[0131] The thickness ratio of the first composition gradient layer 14A in the composition gradient layer 14 is preferably 0.4 to 0.7. This range allows sufficient increase in hole concentration by polarization doping and also provides good contact between the composition gradient layer 14 and the p-type contact layer 15. More preferably, it is 0.4 to 0.6.
[0132] The composition gradient layer 14 is not necessarily a two-layer structure of the first composition gradient layer 14A and the second composition gradient layer 14B, and may be only the first composition gradient layer 14A. Alternatively, it may be a structure of three or more layers with different Al composition change rates, Mg concentrations, etc.
[0133] The thickness of the composition gradient layer 14 is preferably 50% to 90% of the total thickness of the electron blocking layer 13, the composition gradient layer 14, and the p-type contact layer 15. Within this range, the function as the p-type layer can be sufficiently improved.
[0134] The p-type contact layer 15 is located on the composition gradient layer 14. The p-type contact layer 15 is composed of p-GaN. It can be p-AlGaN with an Al composition lower than the minimum Al composition of the composition gradient layer 14, and the Al composition is, for example, less than 50%. In addition, the p-type contact layer 15 can be composed of multiple layers with different Al compositions or Mg concentrations. However, in order to reduce the contact resistance, the uppermost layer in contact with the p-side electrode 16 is preferably p-GaN. GaN absorbs ultraviolet light emitted from the active layer 12, but by making it thin enough, it can transmit a certain degree of ultraviolet light. Therefore, a significant decrease in external quantum efficiency can be avoided. The Mg concentration of the p-type contact layer 15 is, for example, 1×10 20 ~1×10 22 cm -3 The thickness of the p-type contact layer 15 is, for example, 1 to 50 nm.
[0135] A groove having a depth reaching the n-type layer 11 is provided in a part of the surface of the p-type contact layer 15. The groove is provided to expose the n-type layer 11 so as to provide the n-side electrode 17.
[0136] The p-side electrode 16 is arranged on the p-type contact layer 15. The p-side electrode 16 is a reflective electrode that reflects the ultraviolet light emitted from the active layer 12 to the substrate 10 side to improve the light extraction efficiency. The material of the p-side electrode 16 is Ru, Rh, Ni / Au, Ni / Al, ITO / Al, etc. Here, A / B refers to the stacking of A and B in sequence from the p-type contact layer 15 side. In addition, the p-side electrode 16 can be a combination of a transparent electrode such as ITO, IZO, and a DBR (dielectric multilayer film). When a transparent electrode is used, the reflective surface is not the interface between the semiconductor crystal and the electrode, but becomes the interface between the transparent electrode and the reflective electrode. For example, in the case of ITO / Al, the film thickness of ITO must also be considered as the film thickness of the light interference effect. However, the current situation is that there is no electrode that is completely transparent to UVC light, so it is most preferred to form a reflective electrode directly on the semiconductor crystal.
[0137] The n-side electrode 17 is provided on the n-type layer 11 exposed at the bottom surface of the groove. The material of the n-side electrode 17 is Ti / Al, V / Al, etc. Here, A / B means that A and B are stacked in order from the n-type layer 11 side.
[0138] Next, the thickness of each layer in the light-emitting element 1 is described. First, the thicknesses d1 to d3 are set as follows. The total film thickness from the topmost layer in the barrier layer to the p-type contact layer 15 is set to d1, the thickness of the composition gradient layer 14 is set to d2, and the thickness obtained by subtracting d2 from d1 (the total thickness of the topmost barrier layer of the active layer 12, the electron blocking layer 13, and the p-type contact layer 15) is d3 (= d1-d2).
[0139] At this time, d1 is set to satisfy n×d1=m×λ, where n is the average refractive index of the semiconductor layers from the uppermost layer in the barrier layer to the p-type contact layer 15, λ is the emission wavelength, and m is 0.5 to 0.9.
[0140] This formula is a conditional formula for strengthening the ultraviolet light emitted from the active layer 12 to the n-type layer 11 side and the ultraviolet light emitted from the active layer 12 to the electron blocking layer 13 side and reflected by the p-side electrode 16 and then emitted to the n-type layer 11 side through light interference. In addition, in this formula, the range of m is set in a manner that strengthens the ultraviolet light whose emission angle from the active layer 12 is less than the critical angle, taking into account the total reflection at the interface between the upper surface of the light-emitting element 1 and the sealing portion 2. Therefore, if the thickness d1 is set in a manner that satisfies this formula, the on-axis intensity of the light-emitting device can be improved.
[0141] Here, the thickness of the barrier layer of the active layer 12 is determined to be a required value according to the function of confining carriers. In addition, the thickness of the electron blocking layer 13 is determined to be a required value according to the function of blocking electrons. In addition, the thickness of the p-type contact layer 15 needs to ensure that the absorption of ultraviolet light is suppressed as much as possible while obtaining good contact with the p-side electrode 16, and as a result, the thickness is determined to be a specified value. In addition, if the thickness of the electron blocking layer 13 and the p-type contact layer 15 is changed, the series resistance will also change, and the driving voltage of the light-emitting element 1 will also change.
[0142] Generally, the Mg activation rate of Mg-doped AlGaN is very low. Therefore, when the Al composition is constant, the resistance of the film is very high, so the influence of the series resistance on the film thickness is large. On the other hand, the composition gradient layer 14 is a structure that is p-typed by polarization doping, and the film itself has a very low resistance. Therefore, even if the thickness is changed, the influence of the series resistance on the increase of the driving voltage is small.
[0143] Therefore, in Embodiment 1, only the thickness d2 of the composition gradient layer 14 is used as a parameter in the thickness d1, and the thickness d3 other than the thickness d1 is fixed, so that d2 is set in a manner that satisfies n×d2=m×λ-n×d3. By controlling the interference of ultraviolet light by the thickness d2 of the composition gradient layer 14, the increase in the driving voltage of the light-emitting element 1 can be suppressed, and the on-axis intensity of the light-emitting device can be improved.
[0144] In the composition gradient layer 14, it is preferred to set the thickness d2 by varying the thickness of the first composition gradient layer 14A and making the thickness of the second composition gradient layer 14B a fixed value. This is because the second composition gradient layer 14B is Mg-doped, and the change in series resistance when the thickness changes is greater than that of the first composition gradient layer 14A. At this time, the thickness of the second composition gradient layer 14B is preferably a fixed value in the range of 10 to 50 nm.
[0145] The transmittance and reflectance of each layer in the light emitting element 1 with respect to the emission wavelength are preferably set to satisfy the following conditions: By setting the transmittance and reflectance in this way, absorption of light inside the light emitting element 1 can be suppressed, and light extraction efficiency can be improved.
[0146] The transmittance of the substrate 10 as an AlN template is preferably 50% or more. The overall transmittance from the substrate 10 to the p-type contact layer 15 (incident from the substrate side) is preferably 40% or more. The transmittance of the well layer of the active layer 12 alone is preferably 30% or more. The transmittance of the barrier layer of the active layer 12 alone is preferably 50% or more. The transmittance of the electron blocking layer 13 alone is preferably 50% or more. The transmittance of the composition gradient layer 14 alone is preferably 50% or more. In addition, the reflectivity of the p-side electrode 16 is preferably 30% or more.
[0147] It should be noted that the transmittance and reflectance depend on the material, thickness, crystallinity, etc., and the crystallinity depends on the growth conditions such as growth temperature, growth pressure, V / III ratio, growth rate, etc., so the transmittance and reflectance are set according to these various conditions. In addition, the transmittance and reflectance are values at the emission wavelength, which is the case of vertical injection from the substrate 10 side. In addition, the transmittance and reflectance of each layer alone are evaluated in the sample obtained by forming the layer to be evaluated on the substrate 10 as the AlN template.
[0148] As described above, in the light emitting element 1, the interference of ultraviolet light is controlled by the thickness d2 of the composition gradient layer 14, so that the series resistance of the light emitting element 1 changes little. As a result, the increase in the driving voltage of the light emitting element 1 can be suppressed and the on-axis intensity of the light emitting device can be improved.
[0149] 3. Experimental results
[0150] Next, various experimental results related to the light-emitting device of Embodiment 1 are described.
[0151] Experiment 1
[0152] In the light emitting device in the embodiment, ultraviolet light incident on the lens 3 from the light emitting element 1 is considered. Figure 3 (a) and (b) are diagrams schematically showing the path of light inside a simple model of a light emitting device. Figure 3 In (a), AlN, sapphire, air, and lens (quartz) are stacked on the active layer in this order from the active layer side. Figure 3 In (b), AlN, sapphire, fluorine oil, and lens (quartz) are stacked on the active layer in this order from the active layer side. The refractive index of each layer is: AlN is 2.3, sapphire is 1.8, air is 1, fluorine oil is 1.4, and lens is 1.49.
[0153] Figure 3 In case (a), in order to prevent the ultraviolet light from the active layer 12 from being totally reflected at the interface between sapphire and air, the emission angle of the ultraviolet light from the active layer 12 needs to be smaller than 25°.
[0154] on the other hand, Figure 3 In case (b), in order to prevent the ultraviolet light from the active layer 12 from being totally reflected at the interface between sapphire and fluorine oil, the emission angle of the ultraviolet light from the active layer 12 needs to be smaller than 37°.
[0155] according to Figure 3The results show that by filling the space between the back side of the substrate 10 of the light emitting element 1 and the lens 3 with the sealing portion 2, the range of the extracted emission angle can be expanded, and the efficiency of light extraction from the back side of the substrate 10 can be improved. In addition, in order to improve the on-axis intensity of the light emitting device, it is necessary to strengthen the ultraviolet light emitted from the active layer 12 at an emission angle less than 37° through interference.
[0156] Experiment 2
[0157] The light output of light emitting element 1 was calculated using a simplified model, and the conditions for intensifying light by interference when the emission angle was less than 37° were examined.
[0158] Figure 4 (a) and (b) are graphs showing the calculation results of light output. The model is a structure in which an n-type layer, an active layer, a p-type layer, and a reflective electrode are stacked on a substrate in order from the substrate side, and the dependence of the light intensity generated by light interference on the emission angle of ultraviolet light from the active layer 12 under different optical film thicknesses is calculated. The optical film thickness is such that the p-type layer varies between 50nm and 110nm at intervals of 10nm. The emission wavelength is 275nm. Figure 4 (a) is a graph showing the dependence of light intensity at various optical film thicknesses on the emission angle of ultraviolet light from the active layer 12, Figure 4 (b) is a graph showing the thickness dependency of the p-type layer (optical film thickness d1).
[0159] according to Figure 4 As can be seen from (a), when the emission angle is less than 37°, in order to intensify light by interference, the thickness of the p-type layer needs to be 60 to 100 nm.
[0160] Experiment 3
[0161] A light emitting element 1 was prepared in which the thickness of the composition gradient layer 14 was set to various values, and its light output was measured. In addition, the light output was calculated. The layer structure of the light emitting element 1 is as follows from the p-side electrode 16 side to the substrate 10 side. The thickness ratio of the first composition gradient layer 14A to the second composition gradient layer 14B is 1:1.
[0162] p-side electrode 16Ni / Au Ni thickness 10nm Au thickness 50nm
[0163] P-type contact layer 15: Mg-doped GaN, thickness 10 nm
[0164] Second composition gradient layer 14B Mg-doped AlGaN Al composition 75% to 72%
[0165] First composition gradient layer 14A: undoped AlGaN; Al composition: 78% to 75%
[0166] Second electron blocking layer 13B Mg-doped AlGaN Al composition 97% thickness 8.8 nm First electron blocking layer 13A Mg-doped AlN thickness 8 nm
[0167] The barrier layer of the active layer 12 is Si-doped AlGaN. Al composition is 68%. The thickness is 2.5 nm.
[0168] The well layer of the active layer 12 is undoped AlGaN, Al composition is 46%, thickness is 1.7nm
[0169] The barrier layer of the active layer 12 is Si-doped AlGaN. Al composition: 68% and thickness: 9.4 nm.
[0170] Hole blocking layer: undoped AlN, thickness 0.5 nm
[0171] The well layer of the SL layer is undoped AlGaN, Al composition is 46%, thickness is 0.5nm
[0172] SL barrier layer Si-doped AlGaN Al composition 68% thickness 50nm
[0173] n-type layer 11 Si-doped AlGaN Al composition 73% thickness 35nm
[0174] n-type layer 11 Si-doped AlGaN Al composition 73% thickness 150nm
[0175] n-contact layer Si-doped AlGaN Al composition 73% Thickness 1200nm
[0176] Regrowth layer contains GaAlNAl composition 98%Thickness 200nm
[0177] AlN template doped with Ga, thickness 2900nm
[0178] Sapphire thickness 430μm
[0179] Figure 5 The light emitting element 1 (light emitting area: about 550000 μm 2 ) and the measured results when the current is 350mA. Figure 5 The thickness of the p-type layer on the horizontal axis is the thickness of the entire layer from the uppermost layer in the barrier layer to the p-type contact layer 15. Figure 5As shown, it can be seen from the calculation results that by changing the thickness of the composition gradient layer 14, the light output changes periodically, and it is known that an interference effect occurs. In addition, according to the measurement results, it can also be confirmed that by changing the thickness of the composition gradient layer 14, the light output changes due to interference. In addition, the driving voltage VF when 350mA is powered on is 6.15V when the thickness of the p-type layer is the thinnest at 49nm, and 6.35V when the thickness of the p-type layer is the thickest at 107nm, with a difference of 0.2V. The rise in VF caused by the thickening of the p-type layer can be fully suppressed.
[0180] Experiment 4
[0181] As in the implementation method, Figure 5 The light emitting element 1 shown is packaged to form a light emitting device. Figure 6 This is a graph showing the results of measuring the light output of the light emitting device. Figure 6 In the figure, Bare refers to the case of the light emitting element 1 alone, and PKG refers to the case of the light emitting device. Figure 5 Likewise. Figure 6 As shown, it can be seen that by improving the light output of the light emitting element 1, the light output of the packaged light emitting device is also improved.
[0182] Experiment 5
[0183] As in the implementation method, Figure 5 When the light emitting element 1 shown is packaged to form a light emitting device, Figure 7 This is a graph showing the measurement results of the PKG ratio and the width of the emission angle. The PKG ratio is the ratio of the light output of the light emitting device to the light output when only the light emitting element 1 is used. The width of the emission angle is the width of the emission angle of the ultraviolet light from the light emitting device when the intensity of the ultraviolet light calculated from the far field pattern is 0.8 times the maximum intensity. The horizontal axis is the thickness of the p-type layer and the width of the emission angle. Figure 5 same.
[0184] like Figure 7 As shown, it can be seen that when the width of the emission angle is narrowed due to packaging, the on-axis intensity also becomes higher. When the on-axis intensity of the light-emitting device is high, the PKG ratio is also high to 1.3 to 1.6. Therefore, it can be seen that the width of the emission angle is preferably 40 to 80°, and thus the thickness d1 is preferably 60 to 100 nm.
[0185] Experiment 6
[0186] Figure 8 (a) is a graph showing the results of calculating the light output from the upper surface and the light output from the side surface of the light emitting element 1 in Experiment 3. In addition, Figure 8 (b) is a schematic diagram of the light emitting element 1, showing the top surface and the side surface. Figure 5 Likewise. Figure 8 (a) shows that the interference effect of ultraviolet light extracted from the upper surface and the ultraviolet light extracted from the side of the light emitting element 1 is different. In addition, it is known that when the thickness of the p-type layer is in the range of 60 to 100 nm, the overall light output is dominated by the light output from the upper surface.
[0187] Experiment 7
[0188] The energy band diagram and carrier concentration of the light-emitting element 1 are calculated. Fig. 9 (a) and (b) are diagrams showing the energy band diagram of the light-emitting element 1 and the distribution of carrier concentration in the thickness direction. Fig. 9 (a) is the case where no voltage is applied to the light emitting element 1, Fig. 9 (b) is the case where 6 V is applied. Fig. 9 In the figure, thin lines represent the energy band diagram, medium-level lines represent the distribution of electron concentration, and thick lines represent the distribution of hole concentration. Fig. 9 As shown in the figure, except for the area near the p-type contact layer 15, the hole concentration in the composition gradient layer 14 reaches 1×10 16 cm -3 From the above, it was confirmed that the polarization doping turned the material into p-type.
[0189] Experiment 8
[0190] The transmittance and reflectance of each layer in the light emitting element 1 and the entirety were measured, and the absorptivity was calculated. Figures 10 to 17 The following is a graph showing the results. Figure 13 to Figure 16 These layers were formed on the substrate 10 as an AlN template for evaluation. Fig.17 The evaluation was performed by forming a p-side electrode (Ni / Au) on a sapphire substrate. Figures 10 to 16 The UV light was vertically incident from the sapphire side for evaluation. Although the sample is a mirror surface on the incident surface, transmission surface, and reflection surface, it is believed that there is slight scattering. Therefore, it is estimated that the actual transmittance and reflectance are slightly higher than the measured values. Therefore, the following values roughly represent the optical properties of the film.
[0191] Fig.10 This is a graph of sapphire with a thickness of 430 μm. Fig.11 This is a diagram of a substrate in which Ga-doped AlN is formed to a thickness of 3000 nm on sapphire to form an AlN template having a thickness of 430 μm. Fig.10 , the transmittance of sapphire is about 70% at the emission wavelength of 275nm. In addition, according to Fig.11, the transmittance of the AlN template is about 67% at the emission wavelength of 275nm. From the viewpoint of improving the light extraction efficiency from the light emitting element 1, it is considered that the transmittance of sapphire at the emission wavelength is preferably about 60% or more, and the transmittance of the AlN template is preferably about 50% or more. Fig.10 , 11 The results of can confirm that this point is met. The higher the transmittance of the film, the better. In addition to the band gap energy, the transmittance of the crystal layer can be improved by reducing crystal defects or impurities.
[0192] Fig.12 This is a diagram of the entire structure from the substrate 10 to the p-type contact layer 15. The structure of each layer is as shown in Experiment 3. Fig.12 , the transmittance from the substrate 10 to the p-type contact layer 15 is 50% at the emission wavelength of 275 nm. From the viewpoint of improving the light extraction efficiency from the light emitting element 1, it is considered that the transmittance from the substrate 10 to the p-type contact layer 15 at the emission wavelength is preferably 40% or more. Fig.12 By improving the crystal quality of the thicker AlN template or Si-doped AlGaN layer, higher transmittance can be expected.
[0193] Fig.13 This is a graph for the undoped AlGaN (thickness 68nm, Al composition 46%) of the well layer. Fig.14 This is a graph for Si-doped AlGaN (thickness 52nm, Al composition 68%) for the barrier layer. Fig.15 This is a graph for Mg-doped AlGaN (thickness 70 nm, Al composition 97%) of the electron blocking layer.
[0194] according to Fig.13 , the transmittance of undoped AlGaN is 45% at the emission wavelength of 275nm. This AlGaN layer is equivalent to the well layer. Since the thickness of the well layer in the actual light-emitting element is 1.7nm, it is believed that the self-absorption of the emitted light from the light-emitting layer in the well layer is low, and the transmittance is higher than 45%. In view of the above situation, the transmittance of the AlGaN layer with a thickness of 68nm and an Al composition of 46% is preferably above 45%.
[0195] according to Fig.14 , the transmittance of Si-doped AlGaN at a light emission wavelength of 275nm is 60%. This layer is equivalent to a barrier layer and is thicker than the actual film thickness of the light-emitting element of 10nm. Therefore, the transmittance of the barrier layer in the light-emitting element structure is higher than 40%, and the transparency is high. In view of the above, the transmittance of the AlGaN layer with a thickness of 52nm and an Al composition of 68% is preferably above 60%.
[0196] according to Fig.15, the transmittance of Mg-doped AlGaN at the emission wavelength of 275nm is 60%. Even if the AlGaN layer having a bandgap energy higher than the emission wavelength is thicker than the actual film thickness of the light-emitting element, it still has sufficient transmittance. From the viewpoint of improving the light extraction efficiency from the light-emitting element 1, it is considered that the transmittance of the electron blocking layer 13 at the emission wavelength is preferably 60% or more. Fig.15 The results confirm that this point is met.
[0197] Fig.16 This is a graph for the composition gradient layer 14 (thickness 107 nm). The composition gradient layer 14 is a first composition gradient layer 14A, which is undoped AlGaN with Al composition reduced from 78% to 75%, and a second composition gradient layer 14B, which is Mg-doped AlGaN with Al composition reduced from 75% to 73%.
[0198] according to Fig.16 , the transmittance of the composition gradient layer 14 at the emission wavelength of 275nm is 60%. From the viewpoint of improving the light extraction efficiency from the light emitting element 1, it is considered that the transmittance of the composition gradient layer 14 at the emission wavelength is preferably 50% or more. Fig.16 The results confirm that this point is met.
[0199] Fig.17 This is a graph for the p-side electrode 16. The p-side electrode 16 is Ni / Au, with the Ni thickness being 10 nm and the Au thickness being 50 nm. In addition, the evaluation was performed by vertical injection from the Ni side. Fig.17 , the reflectivity at the emission wavelength of 275nm is 30% or more. From the viewpoint of improving the light extraction efficiency from the light emitting element 1, it is considered that the reflectivity of the p-side electrode 16 at the emission wavelength is preferably 30% or more. Fig.17 The results confirm that this point is met.
[0200] (Deformation method)
[0201] In the embodiment, the sealing portion 2 only covers the upper surface of the light emitting element 1, but it may also be Fig.18 As shown, in addition to the upper surface of the light-emitting element 1, the side surface is also covered. By providing the sealing portion 2 on the side surface of the light-emitting element 1, the light extraction efficiency from the side surface of the light-emitting element 1 can be improved. The ultraviolet light extracted from the side surface can be utilized, for example, by being reflected in the axial direction by the reflective material. When the material of the sealing portion 2 is a liquid and a low-viscosity material, a partition wall can be provided around the light-emitting element 1, and the sealing portion 2 can be filled in the area surrounded by the partition wall.
Claims
1. A light emitting device, comprising: A flip chip type light emitting element emitting ultraviolet light, a sealing portion that contacts and covers at least the upper surface of the light emitting element and has a refractive index higher than that of air and lower than that of the light emitting element, and a lens that contacts and covers the sealing portion and has a higher refractive index than the sealing portion, The light emitting element has: The n-type layer is composed of an n-type Group IIIA nitride semiconductor containing Al. The active layer is located on the side opposite to the sealing portion of the main surface of the n-type layer, is composed of a Group IIIA nitride semiconductor containing Al, and has a quantum well structure having a well layer and a barrier layer. an electron blocking layer located on a main surface of the active layer on the side opposite to the n-type layer, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition is higher than that of the barrier layer, a composition gradient layer, located on a side of the main surface of the electron blocking layer opposite to the active layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition decreases as the distance from the active layer increases; a p-type contact layer located on a surface of the main surface of the composition gradient layer on the side opposite to the electron blocking layer, and composed of a p-type IIIA group nitride semiconductor containing Al; and The p-side electrode is located on the side opposite to the composition gradient layer side of the main surface of the p-type contact layer, and reflects ultraviolet light from the active layer. The thickness of the composition gradient layer is set so that light emitted from the active layer to the n-type layer side is enhanced in a direction perpendicular to the main surface of the light-emitting element through interference after being reflected by the p-side electrode from the active layer to the side opposite to the n-type layer.
2. The light emitting device according to claim 1, wherein: The total film thickness from the topmost layer in the barrier layer to the p-type contact layer is set to d1, and the thickness of the composition gradient layer is set to d2. The thickness d2 is set so that d1 satisfies n×d1=m×λ, wherein n is the average refractive index of the layers from the electron blocking layer to the p-type contact layer at the emission wavelength, λ is the emission wavelength, and m is 0.55 to 0.
9.
3. The light emitting device according to claim 1 or 2, wherein: The composition gradient layer is a structure in which a first composition gradient layer and a second composition gradient layer are stacked in sequence from the electron blocking layer side, the first composition gradient layer is undoped or doped with p-type impurities, and the second composition gradient layer is doped with p-type impurities and the p-type impurity concentration is higher than that of the first composition gradient layer.
4. The light emitting device according to claim 3, wherein: The thickness of the composition gradient layer is set according to the thickness of the first composition gradient layer.
5. The light emitting device according to claim 3, wherein: The ratio of the thickness of the first composition gradient layer to the thickness d2 of the composition gradient layer is 0.4 to 0.
7.
6. The light emitting device according to claim 1 or 2, wherein: The sealing portion is provided on the upper surface of the light emitting element but not on the side surface.
7. The light emitting device according to claim 1 or 2, wherein: The electron blocking layer has a structure in which a first electron blocking layer and a second electron blocking layer are stacked in order from the active layer side, and the Al composition of the second electron blocking layer is lower than the Al composition of the first electron blocking layer and lower than the maximum value of the Al composition of the composition gradient layer.
8. A method for manufacturing a light emitting device, the light emitting device comprising: A flip chip type light emitting element emitting ultraviolet light, a sealing portion that contacts and covers at least the upper surface of the light emitting element and has a refractive index higher than that of air and lower than that of the light emitting element, and a lens that contacts and covers the sealing portion and has a higher refractive index than the sealing portion, The light emitting element has: The n-type layer is composed of an n-type Group IIIA nitride semiconductor containing Al. The active layer is located on the side opposite to the sealing portion of the main surface of the n-type layer, is composed of a Group IIIA nitride semiconductor containing Al, and has a quantum well structure having a well layer and a barrier layer. an electron blocking layer located on a main surface of the active layer on the side opposite to the n-type layer, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition is higher than that of the barrier layer, a composition gradient layer, located on a side of the main surface of the electron blocking layer opposite to the active layer side, and composed of a p-type IIIA group nitride semiconductor containing Al, wherein the Al composition decreases as the distance from the active layer increases; a p-type contact layer located on a surface of the main surface of the composition gradient layer on the side opposite to the electron blocking layer, and composed of a p-type IIIA group nitride semiconductor containing Al; and The p-side electrode is located on the side opposite to the composition gradient layer side of the main surface of the p-type contact layer, and reflects ultraviolet light from the active layer. The thickness of the composition gradient layer is set so that light emitted from the active layer to the n-type layer side is enhanced in a direction perpendicular to the main surface of the light-emitting element through interference after being reflected by the p-side electrode from the active layer to the side opposite to the n-type layer.
9. The method for manufacturing a light emitting device according to claim 8, wherein: The total film thickness from the topmost layer in the barrier layer to the p-type contact layer is set to d1, the thickness of the composition gradient layer is set to d2, d3=d1-d2, the thickness d3 is fixed to a specified value, and the thickness d2 is changed to set the thickness d2 in a manner that satisfies n×d1=m×λ, wherein n is the average refractive index of the layers from the electron blocking layer to the p-type contact layer at the emission wavelength, λ is the emission wavelength, and m is 0.55 to 0.
9.
10. The method for manufacturing a light emitting device according to claim 8 or 9, wherein: The composition gradient layer is a structure in which a first composition gradient layer and a second composition gradient layer are stacked in sequence from the electron blocking layer side, the first composition gradient layer is undoped or doped with p-type impurities, and the second composition gradient layer is doped with p-type impurities and the p-type impurity concentration is higher than that of the first composition gradient layer. The thickness of the second composition gradient layer is fixed to a predetermined value, and the thickness of the first composition gradient layer is changed to set the thickness of the composition gradient layer.
